A new species and two new records of the family Phytoseiidae (Acari: Mesostigmata) from Turkey - Döker, İsmai̇l; Kazak, Cengi̇z; Karut, Kami̇l (Zootaxa, 2015)
Phytoseius ibrahimi Döker & Kazak sp. nov. is described and illustrated. The genus Paragigagnathus Amitai & Grinberg, represented by P. insuetus (Livshitz & Kuznetsov), and Neoseiulus neomarginatus Stathakis, Kapaxidi & Papadoulis, are recorded from Turkey for the first time. Identification keys for the Turkish species of Phytoseius Ribaga and Neoseiulus Hughes are provided.